Onset of surface-tension-driven convection in superposed layers of fluid and saturated porous medium - Shivakumara, I.S.; Suma, S.P.; Chavaraddi, Krishna B. (Archives of Mechanics, 2006)
The onset of surface-tension-driven convection is studied in a two-layer system comprising an incompressible fluid-saturated porous layer over which lies a layer of the same fluid. The lower rigid surface of the porous layer is either perfectly heat conducting or insulating, while the upper heat insulating fluid boundary is free and at which the surface tension effects are allowed for. At the contact surface between the fluid-saturated porous medium and the adjacent bulk fluid, both Beavers-Joseph and the Jones conditions are employed. The resulting eigenvalue problem is solved exactly. Besides, analytical expression for the critical Marangoni number is obtained for insulating boundaries by using regular perturbation technique. The effect of variation of different physical parameters on the onset of Marangoni convection is investigated in detail. It is found that the parameter ζ, the ratio of the thickness of the fluid layer to that of the porous layer, has a profound effect on the stability of the system.